Condition Correlation of Coral Reef and Abundance of Indicators Reef Fish in Mandrajaya Water Ciletuh Geopark West Java - Azka Bani Nugraha; Indah Riyantini; Sunarto Sunarto; M. Rudyansyah Ismail (Jurnal Perikanan dan Kelautan, 2019)
The coral reef ecosystem has role as feeding and nursery ground for indicator reef fishes. Coral reef ecosystems in recent years has decline in function, globally the area of coral reefs has decline about 11%. This study aims to analyze the correlation between the condition of life coral reef with the abundance of indicators reef fish. This research was conducted in the waters of Mandrajaya (Ciletuh Geopark) with 5 stations. The method used in this research is Line Intercept Transect (LIT) and Underwater Visual Census (UVC). Data observed were the percentage of live coral and dead coral, as well as the number of indicator reef fish found. Results show that the percentage value of life coral is 51.17% dominated by the CF (Coral Foliose) category, this value shows that the condition of living coral cover is included in the good category. The obtained Mortality Index is worth 0.43 (low), this value is obtained from the ratio of life coral and dead coral. A total number of indicators reef fish is 31 individuals / 1750m² from four species, dominated by Chaetodon octofasciatus (12 individuals). Correlation between life coral cover and abundance of indicators reef fish was positive and had a sufficient relationship on both variables (r = 0.58) with a determinant coefficient of 48%.